ETNOPEDAGOGIC APPROACH IN ELEMENTARY SCHOOL STUDENTS LEARNING - Hoirul Rido (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The ethnopedagogic approach is a learning approach by integrating the values of local cultural wisdom in learning. Given the importance of applying ethnopedagogics, a literature study was made which aims to examine more deeply related to ethnopedagogics, including the nature, urgency, juridical basis, and its implementation in learning in elementary schools. The results of this study indicate that an ethnopedagogic approach is important to maintain local cultural wisdom and as a filter for the entry of foreign cultures as a result of globalization and technological developments. In response to this, the government has formulated several juridical foundations for an ethnopedagogical approach to elementary schools. This is intended so that the insights and values of goodness contained in local local wisdom can be inherited and instilled as early as possible in students.